Yoga does not attenuate speed, agility and change of direction deficit in professional soccer players - Pereira, A. A.; Monteiro, L. F.; Madeira, R. B.; Abel, M. G. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Yoga is an alternative athletic training methodology that may have a positive impact on the recovery of football players due to the physical and psychological impact on restoration processes [1,2,3,4]. However, there is concern that Yoga may reduce football performance due to decreases in rate of force production and agility due to extensive static stretching aspects of Yoga [5]. Indeed, acceleration, deceleration, and change of direction (COD) are critical skills in football performance [6,7]. However, there is limited research evaluating the impact of Yoga on football skill-related performance. Therefore, the purpose of this study was to evaluate the effect of Yoga on football related skills. We hypothesized is that football players undergoing additional Yoga training would not impact speed, agility and change of direction abilities, and therefore may provide a viable strategy to facilitate recovery.